Diffuse panniculitis in a teenage male with ZZ α1-antitrypsin deficiency. Issue 2 (6th March 2023) - Papiris, Spyros A.; Parmaxidis, Anthimos; Theotokoglou, Sofia; Tsakiraki, Zoe; Veith, Martina; Panagiotou, Aikaterini; Pappa, Vasiliki; Kallieri, Maria; Mornex, Jean-François; Katoulis, Alexander C.; Haritos, Dionysios; Panayiotides, Ioannis G.; et al.
Diffuse panniculitis is an inflammatory condition of the subcutaneous fat associated with a multiplicity of aetiological factors and nosological conditions [1, 2]. Diffuse panniculitis commonly occurs spontaneously and presents with painful skin nodules occasionally evolving into skin-ulcerating lesions discharging oily, yellow exudate. Histology shows an inflammatory infiltrate with lobular, septal or combined distribution, depending on the subjacent entity and the timing of biopsy, consisting of neutrophils, lymphocytes, histiocytes or a combination thereof; moreover, foamy macrophages, multinuclear giant cells, granulomas, necrosis or vasculitis may be seen [3]. Diffuse panniculitis is a rare manifestation of α1 -ATD, albeit perhaps the most fulminant and life-threatening complication, associated usually with ZZ phenotype. Intravenous α1 -AT treatment is lifesaving. https://bit.ly/3EDmCzT